2012
DOI: 10.2172/1062652
|View full text |Cite
|
Sign up to set email alerts
|

CO₂ Capture Membrane Process for Power Plant Flue Gas

Abstract: Because the fleet of coal-fired power plants is of such importance to the nation's energy production while also being the single largest emitter of CO 2 , the development of retrofit, post-combustion CO 2 capture technologies for existing and new, upcoming coal power plants will allow coal to remain a major component of the U.S. energy mix while mitigating global warming. Post-combustion carbon capture technologies are an attractive option for coal-fired power plants as they do not require modification of majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They predicted that such studies will shift Robeson's bound to the upper right corner of a Permeability/Selectivity plot having moderate selectivities and high permeabilities. Toy et al (2012), in a project for U.S. Department of Energy, synthesized a vinylidene fluoride (VDF)-based copolymer membrane (VDF-co-B). They observed that the bulky, high-dipole comonomer B helped to increase gas permeability in the polymer matrix, and its greater polarity enhanced the CO 2 affinity (solubility) of the matrix.…”
Section: Non-facilitated Membranesmentioning
confidence: 99%
“…They predicted that such studies will shift Robeson's bound to the upper right corner of a Permeability/Selectivity plot having moderate selectivities and high permeabilities. Toy et al (2012), in a project for U.S. Department of Energy, synthesized a vinylidene fluoride (VDF)-based copolymer membrane (VDF-co-B). They observed that the bulky, high-dipole comonomer B helped to increase gas permeability in the polymer matrix, and its greater polarity enhanced the CO 2 affinity (solubility) of the matrix.…”
Section: Non-facilitated Membranesmentioning
confidence: 99%
“…SO 2 is more condensable than CO 2 and therefore can plasticize the polymer, but it can also compete with CO 2 for sorption sites, leading to a reduction in CO 2 permeability. In tests with a polycarbonate membrane, a short-term test did not reveal any significant impact on CO 2 permeability, but a 20% loss of permeance was shown after continuous exposure to 300 ppm SO 2 over a period of 4 months . Li et al investigated the effect of SO 2 on a facilitated transport membrane using a mixed feed gas containing 5000 ppm SO 2 and showed that the CO 2 permeance declined by 17% and the CO 2 /N 2 selectivity by 20% due to competitive sorption …”
Section: Introductionmentioning
confidence: 99%
“…In tests with a polycarbonate membrane, a short-term test did not reveal any significant impact on CO 2 permeability, but a 20% loss of permeance was shown after continuous exposure to 300 ppm SO 2 over a period of 4 months. 24 Li et al investigated the effect of SO 2 on a facilitated transport membrane using a mixed feed gas containing 5000 ppm SO 2 and showed that the CO 2 permeance declined by 17% and the CO 2 /N 2 selectivity by 20% due to competitive sorption. 25 Nitric oxide in flue gases ranges from 10 to 500 ppm, mostly as NO and traces as NO 2 .…”
Section: Introductionmentioning
confidence: 99%